Identification of ZHOUPI Orthologs in Rice Involved in Endosperm Development and Cuticle Formation - Dou, Mingzhu; Zhang, Yaohua; Yang, Suxin; Feng, Xianzhong (Frontiers in Plant Science, 2018)
The endosperm occupies most of the available space within mature rice seeds, contains abundant nutrients, and directly influences both the quality and quantity of rice production. Initial reports noted that AtZHOUPI (AtZOU) coordinates endosperm breakdown and the concomitant separation of the embryo from this structure in Arabidopsis. The results of this study show that rice genomes contain two most closely related homologs of AtZOU, OsZOU-1 and OsZOU-2; of these, OsZOU-1 expression is limited to within the endosperm where it can be detected throughout this structure five days after pollination (DAP). Its expression gradually decreases from seven DAP to nine DAP. The second of the two most closely related homologs, OsZOU-2, is highly expressed in leaves and stem, but is not detected in developing seeds. Heterologous expression of OsZOU-1 and OsZOU-2 in Atzou-4 mutants also revealed that OsZOU-1 partially complements the seed phenotypes of these individuals, while its counterpart, OsZOU-2, was unable to recover these phenotypes. The over-expression of OsZOU-1 severely disrupts both seed development and plant growth in transgenic rice lines, as plants in which this gene has been knocked down failed in the separation of endosperm from embryo and cuticle formation during seed development. The results of this study therefore suggest that OsZOU-1 is orthologous to the AtZOU, and regulates both endosperm development and cuticle formation in rice.